2018
DOI: 10.17509/ijal.v8i1.11463
|View full text |Cite
|
Sign up to set email alerts
|

Theme markedness in the translation of student translators

Abstract: A good translation product should be able to reflect the typical characteristics of the target language in terms of its function and structure. One of the structure features that can show that the target text (TT) is free from the influence of the structure of the source language (SL) is its theme structure. As there are both marked and unmarked themes, this would be considered as one of the options to characterize the TT structure. This is a research-based article aimed at finding out the extent of theme mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
2
12
1
Order By: Relevance
“…As historical text is a part of recount text, this finding supports Yunita's study, finding the frequent use of simple theme in recount texts [22]. However, this finding is in contrast with Sofyan and Tarigan's study whose findings show that marked theme is the theme most frequently used in Indonesian news item texts [12]. The difference is caused by the nature of news item text that frequently highlights the time and the place of the reported events.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…As historical text is a part of recount text, this finding supports Yunita's study, finding the frequent use of simple theme in recount texts [22]. However, this finding is in contrast with Sofyan and Tarigan's study whose findings show that marked theme is the theme most frequently used in Indonesian news item texts [12]. The difference is caused by the nature of news item text that frequently highlights the time and the place of the reported events.…”
Section: Resultssupporting
confidence: 75%
“…Considering the important role of themes in constructing a text has attracted a number of translation scholars to conduct studies on it. They focused their studies on thematic progression patterns in translation [10,11]; theme markedness in translation [12]; theme characteristics in translation [13]; application of thematic analysis to translation [14,15]; theme and rheme structure in translation [16], and theme choice [17]. The study of theme choice done by Lee is closely related to theme shift, the object studied in this paper, because the choice of theme in the TT might be different from the theme used in the ST [17].…”
Section: Introductionmentioning
confidence: 99%
“…The dominant use of the unmarked theme is also found in the news item text. Sofyan and Tarigan (2018) found that 66% of themes in English news item text were unmarked themes since the readers wanted to know what happened in the news.…”
Section: The Dominant Themes In the Orientation Of Hikayat Deli Textmentioning
confidence: 99%
“…The essential role of theme and rheme in constructing a clause has attracted a number of researchers to conduct a study on it. Previous studies on theme and rheme have different focuses, such as theme markedness (Rosa, 2007a;Sofyan & Tarigan, 2018), thematic progression (Arunsirot, 2013;Jing, 2015;Li, 2011;Rosa, 2007b;Sofyan & Tarigan, 2017;Yunita, 2018), thematic and information structure (Anwar & Amri, 2020;Carter-Thomas, 2002;Potter, 2016). The previous studies mentioned above have tried to find out the characteristics of texts in a certain language or to improve the quality of texts from a textual metafunction point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation